His Promise : an Amish Christmas in Hart County - Gray, Shelley Shepard (Thorndike, Maine : Center Point Large Print, 2018)
"Grace King is pet-sitting when she meets her neighbor, fireman John Michael Miller, who broke her sisters heart five years ago when he walked away from their courtship. Now, as suspicious fires are set in their community, all John Michael wants is to keep Grace safe, hoping they can one day have a future together"--
Keywords: Amish -- Fiction; Arson -- Fiction; Hart County (Ky.) -- Fiction; Romance fiction; Detective and mystery fiction; Christmas fiction; Christmas fiction; Detective and mystery fiction; Fiction; Romance fiction